Lower-dose CT urography (CTU) with iterative reconstruction technique in children – initial experience and examination protocol - Bombiński, Przemysław (International Scientific Literature, Inc., 2014)
BACKGROUND: Conventional X-ray urography is one of the basic imaging techniques in urinary tract diseases in children. CT urography (CTU) employing standard Filtered Back Projection (FBP) reconstruction algorithms is connected with higher radiation dose. Advanced iterative reconstruction techniques enable lowering the radiation dose to the level comparable with conventional X-ray urography with better visualization of the urinary tract. Study protocol and indications for this modified technique should be discussed. MATERIAL/METHODS: Introduction of iterative image reconstruction techniques allowed to significantly reduce the radiation dose delivered during examinations performed at our Department, including CT examinations of urinary tract in children. During the last two years, CT urography replaced conventional X-ray urography and became the basic imaging technique in our Department. We discuss the study protocol regarding pediatric CTU examinations. The main goal is to receive an optimal image quality at reduced radiation dose. RESULTS: CTU examinations performed using the standard filtered back projection (FBP) reconstruction technique are associated with radiation doses about 1.5 times higher than those in conventional X-ray urography. Implementation of iterative reconstruction algorithms in advanced CT scanners allow to reduce the radiation dose to a level comparable or even lower than that in X-ray urography. In addition, urinary tract can be evaluated more precisely in multiplanar reformatted (MPR) and volume rendered (VR) images. CONCLUSIONS: 1. Advanced iterative reconstruction techniques allow to reduce radiation dose in CT examinations and to extend indications for CT urography in children. 2. Urinary tract can be evaluated more precisely in multiplanar reformatted and volume rendered images. 3. CTU may replace conventional X-ray urography in children.